Effect of Annona muricata, Abutilon indicum and Evolvulus alsinoides Extract on Spore Germination of Sorghum Grain Mold Fungi - Basha, S. Ameer; Begum, A. Sajeli; Raghavendra, G. (International Journal of Bio-resource and Stress Management, 2014)
Sorghum grain mold fungi like Alternaria solani, Curvularia lunata, Fusarium moniliforme and Helminthosporium sp, were tested with hexane fraction (AMIE-HF), chloroform fraction (AMIE-CF), ethyl acetate fraction (AMIE-EAF), crude extract (AMIE) of Annona muricata, petroleum ether extract of Abutilon indicum (AIPE) and alkaloid enriched fraction of Evolvulus alsinoides (EAMAA I). AMIE HF at 1000, 2500 and 5000 ppm and AMIE EAF at 2500 and 5000 ppm concentration showed significant effect on F. moniliforme while AMIE CF and AMIE showed no effect. AIPE remarkably inhibited A. solani at all concentrations and C. lunata at 2500 and 5000 ppm concentration. EAMAA I inhibited spore germination of A. solani at 1000, 2500 and 5000 ppm whereas C. lunata at 5000 ppm concentration.